2017
DOI: 10.1111/mec.14086
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular hydrocarbon cues of immune‐challenged workers elicit immune activation in honeybee queens

Abstract: Recently, evidence has shown that variations in the cuticular hydrocarbons (CHCs) profile allow healthy honeybees to identify diseased nestmates, eliciting agonistic responses in the former. Here, we determined whether these 'immunologic cues' emitted by diseased nestmates were only detected by workers, who consequently took hygienic measures and excluded these individuals from the colony, or whether queens were also able to detect these cues and respond accordingly. Healthy honeybee queens were exposed to (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…These secretions can also be transmitted to other individuals by trophallaxis, improving their protection 69 . Such signals of an infection threat have already been described in other social insects, such as termites, that perform a vibrational display to increase their distance from the non-infected nestmates 70 , and honeybees, in which the cuticular chemical cues of the diseased nestmates can induce an immune response in queens 71 .…”
Section: Discussionmentioning
confidence: 73%
“…These secretions can also be transmitted to other individuals by trophallaxis, improving their protection 69 . Such signals of an infection threat have already been described in other social insects, such as termites, that perform a vibrational display to increase their distance from the non-infected nestmates 70 , and honeybees, in which the cuticular chemical cues of the diseased nestmates can induce an immune response in queens 71 .…”
Section: Discussionmentioning
confidence: 73%
“…Upon detection, healthy animals usually respond by interacting with sick conspecifics less or avoiding them completely ( Poirotte et al, 2017 ; Kiesecker et al, 1999 ; Behringer et al, 2006 ; Anderson and Behringer, 2013 ). In addition, they may prophylactically increase the expression of their immune defences in preparation for a potential immune challenge ( Hernández López et al, 2017 ), and a similar phenomenon is observed in animals and plants in response to chemicals released by wounded conspecifics ( Heil and Silva Bueno, 2007 ; Peuß et al, 2015 ). Because there are downsides to being socially excluded, sick animals may, under some circumstances, attempt to hide their illness ( Lopes, 2014 ; Lopes et al, 2012 ).…”
Section: Introductionmentioning
confidence: 89%
“…Chemoreception is able to facilitate social immunity by influencing not only the behavior defense, but also the physiological defense. In bees, societal members can immunize themselves by directly contacting with cuticular hydrocarbon (CHC) cues of immune-challenged workers [121,122,123], indicating a potential route to social immunization against bacterial pathogens in social insect societies. In addition, it has been reported that social transfer of low-dose fungal conidia promotes social immunization in social insects [14,62].…”
Section: Mechanism Of Social Immunitymentioning
confidence: 99%